2018
DOI: 10.1002/adfm.201705970
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Self‐Driven, Air‐Stable, and Broadband Photodetector Based on Vertically Aligned PtSe2/GaAs Heterojunction

Abstract: Group-10 layered transitional metal dichalcogenides including PtS2, PtSe2 and PtTe2 are excellent potential candidates for optoelectronic devices due to their unique properties such as high carrier mobility, tunable bandgap, stability and flexibility. Large-area platinum diselenide (PtSe2) with semiconducting characteristics is far scarcely investigated. Here, we report on the development of a high performance photodetector based on vertically aligned PtSe2-GaAs heterojunction which exhibited a broadband sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
187
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 372 publications
(204 citation statements)
references
References 64 publications
9
187
1
Order By: Relevance
“…(Please see the detailed calculation process in the Supporting Information.) The responsivity is much better than other group‐10 TMDs based device including PtSe 2 /GaAs and PdSe 2 /Si …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…(Please see the detailed calculation process in the Supporting Information.) The responsivity is much better than other group‐10 TMDs based device including PtSe 2 /GaAs and PdSe 2 /Si …”
Section: Resultsmentioning
confidence: 90%
“…Further device analysis reveals that the PdSe 2 /GeNC arrays device exhibits obvious sensitivity to repeatable 1350, 1550, 1650, and even 2200 nm illumination with good reproducibility. Specifically, the responsivity is estimated to be 530.2 mA W −1 , which is much better than other group‐10 TMDs based device including PtSe 2 /GaAs and PdSe 2 /Si . What is more, the specific detectivity under 1550 nm illumination is 1.45 × 10 11 Jones, respectively.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The newly discovered group 10 TMDs layered materials such as platinum diselenide (PtSe 2 ) and platinum disulfide (PtS 2 ) have recently attracted great attention, which have been demonstrated to be capable of enabling high performance optoelectronic devices due to their high carrier mobility and broadband light absorption [23][24][25]. The potential applications of layered PtX 2 have already been demonstrated in photocatalyst [23] and field-effect transistors [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown some intriguing properties of PtSe 2 , such as high charge‐carrier mobility, intrinsic patterning, piezoresistivity, and spin‐layer locking . Moreover, PtSe 2 exhibits great potential in electronic and optoelectronic devices, for example, field effect transistors (FETs), spintronics, mid‐infrared photodetectors, gas sensors, valleytronics, and optical modulators . Despite a number of reports addressing the synthesis, electrical properties, and prototype devices, there is still a lack of understanding regarding the carrier dynamics in layered PtSe 2 on an ultrafast time scale.…”
mentioning
confidence: 99%